Intersections of Multiculturalism, Education, and Identity in 'Entre les Murs’: A Comparative Analysis of Learning Experiences (Global Journal of Cultural Studies, 2023)
This scholarly article delves into the intricate layers of the French banlieue film Entre les murs (2008), directed by Laurent Cantet. The article aims to unravel the multifaceted portrayal of banlieue culture and its significance within the cinematic and socio-cultural landscape. It comprehensively analyses the film's narrative, characters, social themes and artistic choices, navigating the complexities of cultural diversity and identity formation within the banlieue context. The film's characters, students, and teachers become focal points for analysis, shedding light on the challenges and possibilities within the education system.Further, the article explores the film's cinematic techniques and aesthetics, including its visual style, cinematography, editing, and use of sound and music. The documentary-like approach of the film is examined, considering its impact on the storytelling and the portrayal of authenticity. By analysing the film's artistic choices, this article aims to uncover the subtle nuances and intentional creative decisions that contribute to the film's overall impact.Moreover, the article evaluates the critical reception and lasting legacy of Entre les murs. It explores the film's reception among critics and audiences, highlighting its awards, nominations, and influence on subsequent French cinema. It also discusses the film's socio-political relevance and contribution to the discourse on education, multiculturalism and social inequality.In addition to drawing upon various scholarly works and theories, the article seeks to place Entre les murs within the broader academic discourse, including areas such as auteur theory, social realism, postcolonial theory, cultural studies and sociological perspectives. Together, these serve to deepen the understanding of the film and its socio-cultural implications.Regarding the social context, the article examines the film's position in time-space and the situation of the French educational system in the poor and multicultural neighbourhoods of France. It considers the challenges faced by the education system and explores the plans to address them, contributing to a comprehensive analysis of the film's socio-cultural context.In conclusion, this academic article unveils the depths of Entre les murs, shedding light on its portrayal of banlieue realities, the educational system's challenges, and the complexities of multiculturalism and identity. By combining meticulous analysis, scholarly perspectives and an appreciation for the film's artistic merits, this article contributes to the ongoing academic dialogue surrounding the film and its enduring impact on French cinema.